Giving Drugs a Second Chance: Overcoming Regulatory and Financial Hurdles in Repurposing Approved Drugs As Cancer Therapeutics - Hernandez, J. Javier; Pryszlak, Michael; Smith, Lindsay; Yanchus, Connor; Kurji, Naheed; Shahani, Vijay M.; Molinski, Steven V. (Frontiers in Oncology, 2017)
The repositioning or ‘repurposing’ of existing therapies for alternative disease indications is an attractive approach that can save significant investments of time and money during drug development. For cancer indications, the primary goal of repurposed therapies is on efficacy, with less restrictions on safety due to the immediate need to treat this patient population. This report provides a high-level overview of how drug developers pursuing repurposed assets have previously navigated funding efforts, regulatory affairs, and intellectual property laws to commercialize these ‘new’ medicines in oncology. This article provides insight into funding programs (e.g. government grants, philanthropic organizations) that academic and corporate initiatives can leverage to repurpose drugs for cancer. In addition, we highlight previous examples where secondary uses of existing, FDA- or EMA-approved therapies have been predicted in silico and successfully validated in vitro and/or in vivo (i.e. animal models and human clinical trials) for certain oncology indications. Lastly, we describe the strategies that the pharmaceutical industry has previously employed to navigate regulatory considerations and successfully commercialize their drug products. These factors must be carefully considered when repurposing existing drugs for cancer to best benefit patients and drug developers alike.